The influence of Quizziz-online gamification on learning engagement and outcomes in online English language teaching - Nina Inayati; Alimin Adi Waloyo (Journal on English as a Foreign Language, 2022)
Game-based English learning was considered as one of the effective techniques to develop student learning motivation and engagement. It is popular due to today's more advanced gadget technology and the COVID-19 pandemic requiring students to study from home. Much research on the gamification of English learning in various countries involving different age levels was conducted. However, very few research focused on Quizziz-online gamification for English learning purposes in the context of junior high students. This research investigated the level of students' engagement and learning outcomes of Quizziz-online gamification on English learning development in junior high school. This case study involved a secondary school English teacher and 62 students in the 9th grade at a private junior high school in Batu City, East Java Province, Indonesia. The data collection methods were observation, interview, and students' test results. Based on the descriptive and thematic analysis, it was found that gamification affected students' engagement, better active participation, and discipline. However, their English learning outcomes were dynamic. Thus, integrating an internet-based game, Quizziz, in English instruction with more cognitively driven approaches is worth implementing for better English outcomes.